PRELIMINARY ESTIMATION OF THE PRINCIPAL DIMENSIONS OF OFFSHORE SUPPLY VESSEL BASED ON UPDATED STATISTICS - Mohamed Ahmed; Ahmed Naguib; ELsayed Hegazy (Port Said Engineering Research Journal, 2012)
There are many formulae for estimating the principal dimensions of OSVs (offshore supply vessels) depending on previous data of existing ships. Some formulae are not suitable for modern design, because of the great development in ship engineering. Therefore, it was necessary to get new formulae to estimate the principal dimensions of OSVs. The aim of this paper is to introduce and update the data that can be used to quickly predict the main dimensions of OSVs in preliminary (basic/pre-contract) design stage. For this purpose, data from statistical survey of 80 existing modern OSVs have been reviewed and reintroduced in the form of charts and equations .Finally, it has to be noted that these charts and equations need to be updated from time to time to cope with the continuous developments in the industry of OSVs . The obtained results were compared with previous formulae, and it was found that the obtained results are closer to the existing unit particulars